2022
DOI: 10.3389/fpubh.2022.857246
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association Between Problematic Mobile Phone Use and Eating Disorder Symptoms and the Mediating Effect of Resilience in Chinese College Students: A 1-Year Longitudinal Study

Abstract: A previous cross-sectional study found that problematic mobile phone use (PMPU) was associated with students' eating disorder symptoms. However, since the cross-sectional study cannot infer the causality and the direction of effect, the longitudinal relationship between the two and the mechanism behind this relationship are unclear. Therefore, the present study explores the prospective association between PMPU and eating disorder symptoms and related mediation mechanisms using a 1-year longitudinal study of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Previous studies found that self-control regulates the correlation between PA and MPA. Factors such as negative emotions (eg, anxiety [ 69 , 70 ] and loneliness [ 71 , 72 ]) and mental toughness [ 73 , 74 ] have been shown to affect the relationship between PA and MPA. We speculate that these factors may modulate the relationship between PA and MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that self-control regulates the correlation between PA and MPA. Factors such as negative emotions (eg, anxiety [ 69 , 70 ] and loneliness [ 71 , 72 ]) and mental toughness [ 73 , 74 ] have been shown to affect the relationship between PA and MPA. We speculate that these factors may modulate the relationship between PA and MPA.…”
Section: Discussionmentioning
confidence: 99%
“…Each subscale was graded separately and then a total RQ score was summed. Emotional stability was scored as, lower-than-(< 27), normal (27)(28)(29)(30)(31)(32)(33)(34), and higher-than-normal (> 34). Willpower was scored as, lower-than-(< 14), normal (14-19), and higher-thannormal (> 19), and problem-solving as, lower-than-(< 13 normal (13-18), and higher-than-normal (> 18).…”
Section: Measurementmentioning
confidence: 99%
“…29 However, few studies have examined protective effect of these factors against negative effect of SM use, particularly on eating-related problems. 30,31 There are many studies that found an association between SM activities and eating problems. However, most of them usually found an association between a few specific SM activities and eating-related problem as previously mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is an important psychological resource that helps maintain mental health [ 40 ]. Stressful life events affect coping styles and resilience, making people more likely to suffer adverse mental and psychological consequences [ 41 ].…”
Section: Introductionmentioning
confidence: 99%